RANCANG BANGUN SISTEM INFORMASI PENYEWAAN KONTRAKAN MUTIARA BERBASIS WEB - Andika Nova Suryadi; Nasirudin (Jurnal Informatika Teknologi dan Sains, 2022)
Rented rentals really need an information system, because the current rental process is still manual, namely looking for a rented house can still be ordered, the owner does not place advertisements on the roadside near the rented house. This manual method will greatly affect the time factor, where the owner will wait for the tenant to come and the prospective tenant must go out to look for empty waste. Therefore, the author took the initiative to create a web-based rental information system design using PHP and MySql. PHP and Mysql programming are synergistic languages ??and databases, and the design of this system uses the waterfall method, so that the design of this system is suitable for use as a rental booking system. So this research is able to provide all detailed information related to rented houses.